A vinculatividade dos precedentes judiciais aos conselhos de contribuintes - Macedo, Ludmilla Nascimento Correia (2023)
This work seeks to demonstrate the binding nature of Taxpayer Boards to judicial precedents. The issue arises from the text of Article 927 of the Brazilian Civil Procedure Code of 2015, which does not explicitly bind the Public Administration to the precedent model outlined in the code, but only judges and courts. Considering this, a scientific hypothesis is raised that the binding nature of Taxpayer Boards to precedents can be asserted regardless of the absence of express (or literal) normative authorization in the laws and regulations governing their respective operations. The first chapter focuses on understanding the precedent model in Brazil’s legal system, starting from theory to explain that precedents originates from stare decisis, which involves respecting previous judicial decisions that resolved similar cases. The research seeks to demonstrate the normative nature of precedents as a source of law, highlighting the importance of identifying ratio decidendi, the necessary grounds for the judgment of the issue, and explores the technique of distinction and the possibility of overcoming the precedent as a method make the system flexible. The second chapter addresses the influence of judicial precedents on the Public Administration, arguing that the she must observe the procedural duties imposed by the theory of precedents, avoiding the uncritical repetition of arguments already overcome by the Judiciary. This is based on the precedent model established by the Civil Procedure Code, which aims at stability, coherence, and integrity of decisions, leading to the understanding that the Public Administration is subject to binding precedents due to the combination of constitutional principles and the rules established in the procedural code. The third chapter outlines the role of Taxpayer Boards, including the Administrative Council for Tax Appeals (known in Brazil as “CARF”) and the Boards of States and Municipalities in the context of tax administrative proceedings. They play a crucial role in the analysis of appeals related to tax assessments and penalties, as well as in the legality control of tax assessments. Furthermore, they are responsible for avoiding unnecessary litigation and contributing to legal unity. The research argues that the binding nature of Taxpayer Boards to precedents is related to the respect for constitutional norms that determine legality, legal certainty, good faith, protection of legitimate trust, morality, and administrative efficiency. It is argued that, by observing judicial precedents, the Public Administration not only reduces the judicialization of disputes and promotes legal unity but also ensures equality and legal certainty. In conclusion, the research emphasizes that theoretical objections to the binding nature of Taxpayer Boards to judicial precedents do not deny the need for a formal precedent model, especially regarding the coherence of the legal system. The administrative instance must respect judicial precedents, under penalty of undermining its authority and becoming merely a preliminary stage before access to the Judiciary. Therefore, adherence to precedents is a mandatory rule for Public Administration.